Therapeutic Hypothermia and Leukocytosis in Newborns: An Unusual Association. Issue 8 (November 2020) - De Rose, Domenico Umberto; Lazzareschi, Ilaria; Serrao, Francesca; Maggio, Luca; Coppola, Maria; Hindocha, Hirvi; Vento, Giovanni; Gallini, Francesca
Abstract : Therapeutic hypothermia is a standardized intervention for the treatment of moderate-severe hypoxic-ischemic encephalopathy in newborns with gestational age ≥35 weeks. Several complications have been described. Our aim was to report a case of leukocytosis, for the first time in the literature, in a term newborn who underwent therapeutic hypothermia.